Wisespot, a novel approach for wireless localization of damages in bridges - Onoufriou, Toula; Kounoudes, Anastasis; Milis, Marios; Kalis, Antonis; Tragas, Philippos; Constantinides, Anthony G.; Votsis, Renos (My University, 2012)
Despite the significant increase of applications for Wireless Sensor Networks (WSN) in various industries, their use in the infrastructure monitoring industry remains low, and this is mainly due to the limitations introduced by the current technology of wireless nodes. More specifically, wireless nodes currently used in WSN have significant limitations in energy consumption, communication range, cost, and localization efficiency. These limitations impede their wide integration in applications such as health monitoring of large infrastructures (bridges, tunnels, water supply systems, transport networks, etc.), environmental control and many other industries, requiring deployment of sensor nodes on a large scale. The WiseSPOT research project developed a new generation of compact low-power wireless sensor nodes that utilize advanced smart antenna technology for continuous monitoring, localization and tracking of events in the network environment (i.e, crack detection in large structures, land movements in landslide prediction etc.). This technology is intended to develop a powerful remote monitoring tool for structural civil engineers that can be used for continuous monitoring of the health of large structures such as bridges, dams, the transportation and utilities infrastructure.
Keywords: Civil engineers; Wireless sensor networks; Environmental control